Assembling phthalocyanine dimers through a platinum(II) acetylide linker - Jimenez, Angel J.; Luisa Marcos, M.; Hausmann, Anita; Salome Rodriguez-Morgade, M.; Guldi, Dirk Michael; Torres, Tomas (Chemistry - A European Journal, 2011)
Phthalocyanine (Pc) dimers connected through trans-platinum(II) diacetylide linkers have been prepared by reaction of the corresponding ethynylphthalocyanines with trans-bis(triethylphosphine)platinum(II) chloride. Special emphasis was placed on the analysis of the ground- and excited-state features of these compounds in relation to butadiyne-bridged Pc dimers and the corresponding monomers. Both Zn -containing Pc dimers exhibit long-lived triplet excited states. The insertion of σ-bonded trans-platinum(II) diacetylide spacers decoupled the two Pc groups and led to an appreciable acceleration (by a factor of up to 10) of the radiative and nonradiative decay rate of the singlet and triplet excited states. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.